The College Admissions Problem Revisited - Roth, Alvin E.; Sotomayor, Marilda (Econometrica, 1989)
The college admissions problem is perhaps the simplest model of many-to-one matching in two-sided markets, such as labor markets. The authors show that the set of stable outcomes (which is equal to the core defined by weak domination) has some surprising properties not found in models of one-to-one matching. These properties may help to explain the success that this kind of model has had in explaining empirical observations. Copyright 1989 by The Econometric Society.